A arquitetura enunciativa em “O Monstro” de Sérgio Sant’anna - Guimarães, Inaura (2009)
This paper focuses on the study of the short story “O Monstro” of the homonymous masterpiece by Sérgio Sant’Anna (1994) and has as its foundation the theoretical reference of French semiotics. Our goal is to analyze the enunciating architecture of the masterwork, which refers to the actors’ constructions and to the passion that leaded their actions. In this sense, we have noticed the relationship that is processed between the instance of the enunciation and the enunciate discourse, aiming at unraveling the enunciating strategies, created by the enunciator in order to validate the enunciate text. In addition, we have sought to conduct an analysis of the path of the actor Antenor Lott Marçal, as an enunciate subject and as a narrating subject, projected at the current time of the enunciation. In the former, he is endowed of a thematic role of monster for having murdered the young Frederica Stucker along with his mistress Marieta de Castro. In the latter, he evaluates his narrative route in the simulacrum of the interview that constitutes the text. In this sense, we have observed the way in which the enunciator calls upon the structure of the journalistic interview reconstructing it as a literary text and the signifying practices which emerge from this dialogue. We also describe the narrative, cognitive and patemic paths of the characters Marieta and Antenor, focusing on the passions that supposedly motivate their actions, such as power, envy, jealousy, anger and revenge, all of which are bad passions. On the other hand, when we analyze the figurative paths of the text, we notice that the violence themes in the interpersonal relationships is highlighted in the masterpiece through an ironic look of the enunciation subject that leads us to question the worth of the values embedded in the contemporary society. Keywords: Sérgio Sant’Anna; enunciation; enunciate; actor; passion